2011
DOI: 10.2147/jmdh.s19315
|View full text |Cite
|
Sign up to set email alerts
|

What patients want and need to know about atrial fibrillation

Abstract: Clinicians in a variety of settings are called upon to care for patients diagnosed with atrial fibrillation (AF), a common chronic condition that affects up to 3 million people in the USA. Evidence-based guidelines provide clinicians with direction for treatment of AF, but recommended content for educating patients and counseling about self-management of AF is not included in published guidelines. When patients believe they have a good understanding of AF they report fewer symptoms, perceive greater control ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
2
28
0
1
Order By: Relevance
“…Increased emotional distress and feelings of uncertainty related to arrhythmia have been reported by others [26, 28]; however, our study also found that some patient felt that their arrhythmia cause a negative impact on family life and led to feelings of isolation, which has been poorly described in previous literature. Our study found 40 % of participants reported a perceived negative impact on family and close friends due to their condition, often leading to feelings of guilt and further isolation for the patient as they felt compelled to withdraw from some family and social occasions.…”
Section: Discussionsupporting
confidence: 61%
“…Increased emotional distress and feelings of uncertainty related to arrhythmia have been reported by others [26, 28]; however, our study also found that some patient felt that their arrhythmia cause a negative impact on family life and led to feelings of isolation, which has been poorly described in previous literature. Our study found 40 % of participants reported a perceived negative impact on family and close friends due to their condition, often leading to feelings of guilt and further isolation for the patient as they felt compelled to withdraw from some family and social occasions.…”
Section: Discussionsupporting
confidence: 61%
“…Poznanie punktu widzenia chorych, a także ich nastawienia do AF i jego leczenia może umożliwić poprawę leczenia AF oraz jego wyników [1017]. Obejmuje to odpowiednio dostosowaną edukację pacjentów koncentrującą się na chorobie, rozpoznawaniu objawów, leczeniu, poddającym się modyfikacji czynnikom ryzyka AF, a także aktywnościach związanych z samoleczeniem [1018,1019].…”
Section: Zintegrowana Edukacja Pacjentówunclassified
“…1017 This includes tailored patient education focusing on the disease, symptom recognition, therapy, modifiable risk factors for AF, and self-management activities. 1018,1019 14.3 Self-management and shared decision-making Self-management is primarily focused on tasks to manage the condition, such as adhering to a therapeutic regimen or modifying behaviour (e.g. resulting in smoking cessation or weight loss).…”
Section: Integrated Patient Educationmentioning
confidence: 99%